2018
DOI: 10.3201/eid2406.170715
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease in the Middle East Caused by an A/ASIA/G-VII Virus Lineage, 2015–2016

Abstract: Phylogenetic analyses of foot-and-mouth disease type A viruses in the Middle East during 2015–2016 identified viruses belonging to the A/ASIA/G-VII lineage, which originated in the Indian subcontinent. Changes in a critical antigenic site within capsid viral protein 1 suggest possible evolutionary pressure caused by an intensive vaccination program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 14 publications
3
37
1
Order By: Relevance
“…High evident rRT-PCR results associated with samples that had CT values above the diagnostic threshold CT was sufficient for the confirmation of FMDV prevalence, this study had a beneficial result where FMD was endemic. Also, rRT-PCR able to identify and characterized different FMDV serotypes causes outbreaks (Bachanek-Bankowska et al, 2018). RRT-PCR results was similar to the result obtained by 3ABC ELISA and RT PCR.…”
Section: Resultssupporting
confidence: 78%
“…High evident rRT-PCR results associated with samples that had CT values above the diagnostic threshold CT was sufficient for the confirmation of FMDV prevalence, this study had a beneficial result where FMD was endemic. Also, rRT-PCR able to identify and characterized different FMDV serotypes causes outbreaks (Bachanek-Bankowska et al, 2018). RRT-PCR results was similar to the result obtained by 3ABC ELISA and RT PCR.…”
Section: Resultssupporting
confidence: 78%
“…The isolates BAN/GA/ Sa-197/2013 (BAN-197) and The complete VP1-based phylogeny revealed all our isolates clustering within the same sublineage C under the lineage A/ASIA/ G-VII (Figure 1). The findings of the reconstructed phylogenetic tree corroborated with the previous studies (Al Bachanek-Bankowska et al, 2018;Nandi et al, 2015). The field isolates BAN-307 and BAN-310 have 99% and 97% VP1 coding sequence identity, respectively, with BAN-304 (the field isolate used as a vaccine strain in this study).…”
Section: Circulating Fmdvs Belong To the Sublineage A/ Asia/g-vii Csupporting
confidence: 89%
“…In 2015, FMDV serotype A viruses from the A/ASIA/G-VII lineage (further denoted as G-VII), were detected in a number of countries in the Middle East. Sequence analysis revealed a close genetic relationship (>95% VP1 nucleotide identity) between viruses recovered from these outbreaks to FMD viruses circulating in South Asian countries, such as India and Bangladesh [3], and also demonstrated that these viruses were distinct (<84% VP1 nucleotide identity) from the A/ASIA/Iran-05 viruses that are endemic in the Middle East [4].…”
Section: Introductionmentioning
confidence: 88%